2011
DOI: 10.1099/jmm.0.029736-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diversity of Clostridium difficile strains in infants

Abstract: During early infancy asymptomatic intestinal colonization by Clostridium difficile is frequent. To update information on infant colonization prevalence and to characterize infant strains, in terms of their virulence factors and their phylogenetic diversity, a prospective screening of C. difficile in the stools of infants 0 to 2 years old was conducted at Jean Verdier Hospital (Hô pital Jean Verdier) over an 18 month period. C. difficile was screened by toxigenic culture, and molecular characterization was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 32 publications
3
58
3
5
Order By: Relevance
“…Among newborns and healthy infants, carriage rates may be as high as 84.4 % up to age 2 years ( 199,201,202 ). Some infants may have non-toxigenic strains.…”
Section: Appendixmentioning
confidence: 99%
“…Among newborns and healthy infants, carriage rates may be as high as 84.4 % up to age 2 years ( 199,201,202 ). Some infants may have non-toxigenic strains.…”
Section: Appendixmentioning
confidence: 99%
“…Meanwhile, the proportion of toxin positivity as assessed by PCR assays using total bacterial genomic DNA as a template was 25-37.5%, which corresponded to the lowest value reported in previous studies (33-100%) using both culture and direct fecal cytotoxin detection in cultured cells [10,19,26]. It has been reported that many asymptomatic infants under 2 years of age are frequently colonized with both nontoxigenic and toxigenic strains [10,38].…”
Section: Discussionmentioning
confidence: 75%
“…It has been reported that many asymptomatic infants under 2 years of age are frequently colonized with both nontoxigenic and toxigenic strains [10,38]. The reported proportion of toxigenic strains is 21-37.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In premature neonates, if clostridia are the most common anaerobes found in fecal samples during the first 2 months of life (3)(4)(5)(6)(7), then asymptomatic intestinal carriage of toxigenic or nontoxigenic strains is common and not systematically associated with infections, particularly for C. difficile (8,9). However, various clostridial species have been recovered in neonatal bacteremia (10), and several reports have suggested the role of clostridia in the pathogenesis of necrotizing enterocolitis (NEC) (11)(12)(13)(14), a devastating neonatal gastrointestinal disease with high morbidity and mortality rates (15).…”
mentioning
confidence: 99%